Impacts of PV module distribution in large scale solar infrastructures - Ya'acob, Mohammad Effendy; Lu, Li; Anuar, Shamsul; Mohtar, Mohd Nazim; Othman, Noor Fadzlinda; Zabidin, Zamzuri; Hizam, Hashim (IEEE, 2022)
Photovoltaic (PV) system which is the most prominent green energy in Malaysia currently comprises of multiple components combine into building of systems (BoS) to generate Direct Current (DC) generations. The PV system can be configured to suit a wide range of application in domestic consumer residence, industry machineries, agriculture activities and other stand-alone equipment with various power ratings. The performance of a PV system largely dependent on sun insolation level, weather condition, BoS configuration and the types of loads to be connected. The IEC 61724 standard calculates the PV performance ratio and performance index based on the ratio of actual solar PV system output and the expected values. This work shares some typical concern on the DC Generation pattern for each individual PV inverters configured in a large-scale solar PV farms in Puchong, Selangor within 5 acres area. Generally, PV modules which is located on the centre-point of a large scale solarfarms (LSS) would produce the least DC power at any point of sun hours mainly due to the accumulated hot air passing thru the PV strings. The hot air would eventually reduce the DC generation and also the conversion efficiency. Unfortunately, this information has not been studied and quantified to project a major concern in solar PV operation. Thus, this study provides the actual energy data mapping for continuous 31 days collection in December 2021 based on the location of each string in large scale solar PV farms.